2008
DOI: 10.1192/bjp.bp.107.042069
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of suicide in Karachi, Pakistan

Abstract: Suicide in Pakistan is strongly associated with depression, which is under-recognised and under-treated. The absence of an effective primary healthcare system in which mental health could be integrated poses unique challenges for suicide prevention in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 20 publications
(32 reference statements)
9
111
2
4
Order By: Relevance
“…We assessed 29 (78%) studies to be of high [30][31][32][33][34][35][36][37][38][39][40][41][42][43] or acceptable [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] quality (Table 3). Eight studies [59][60][61][62][63][64][65][66] were of low quality due to problems with risk of bias: performance, attrition and detection bias (interrupted-time series); selection bias, unclear case definitions, detection bias, lack of adjustment for confounding factors (case-control studies); detection bias, lack of adjustment for confounding factors (cross sectional and ecological studies).…”
Section: <Figure 1> <Table 2>mentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed 29 (78%) studies to be of high [30][31][32][33][34][35][36][37][38][39][40][41][42][43] or acceptable [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] quality (Table 3). Eight studies [59][60][61][62][63][64][65][66] were of low quality due to problems with risk of bias: performance, attrition and detection bias (interrupted-time series); selection bias, unclear case definitions, detection bias, lack of adjustment for confounding factors (case-control studies); detection bias, lack of adjustment for confounding factors (cross sectional and ecological studies).…”
Section: <Figure 1> <Table 2>mentioning
confidence: 99%
“…Six 31,38,49,51,59,62 focused on completed suicide and six 30,32,39,41,46,54 on non-fatal SIB, with one 52 looking at both dimensions. Among the seven studies reporting on completed suicide, three 31,51,62 reported a positive and one 38 a null association between completed suicide and unemployment using bivariate analysis.…”
Section: Unemploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…Married status as a protective factor and a risk factor for suicide has also been reported in other countries. In India, Pakistan, and Iran, being married appeared to a risk factor for suicide, especially for women [21][22][23] . However, most studies from Asia, Europe, New Zealand, and the United States have shown that married status had some protective effect against suicide, especially for men [6,[16][17][18][19][28][29][30][31] .…”
Section: Issn 2372-5923mentioning
confidence: 99%
“…Similarly, being unmarried has also been identified as a risk factor for suicide in the majority of previous studies [1,[16][17][18][19][26][27][28][29][30][31] . However, in India, Pakistan, and Iran, majority of suicide victims were married and being married was even a risk factor for suicide, especially in women [21][22][23] . History of mental illness has also been reported as a robust risk factor for suicide in developed counties [1,25] , but in China, more than 47% suicide victims did not have a psychiatric diagnosis at the time of death [4,[32][33][34] .…”
mentioning
confidence: 99%